ChemInform Abstract: Direct Arylation of Phenanthroline Derivatives via Oxidative C—H/C—H Cross‐Coupling: Synthesis and Discovery of Excellent Ligands. Issue 28 (21st June 2013) - Li, Bijin; Qin, Xurong; You, Jingsong; Cong, Xuefeng; Lan, Jingbo
Abstract A protocol for the synthesis of aryl functionalized phenanthrolines (I) is developed.